IS CEREBRAL AMYLOID ANGIOPATHY A PRECIPITATING EVENT IN THE ETIOLOGY OF ALZHEIMER'S DISEASE. (20th December 2022) - Edland, Steven; Zarow, Chris; Shifflett, Benjamin; Flanagan, Margaret; White, Lon
Abstract: Amyloid plaque and cerebral amyloid angiopathy (CAA) are early neuropathologic changes observed in the setting of clinical Alzheimer's disease (AD), typically preceding biomarker evidence of intraneuronal tau neurofibrillary tangle (NFT) development and associated cognitive decline. Here we apply structural equation models to explore the potential causal associations between amyloid-beta lesions (i.e. plaques and CAA) and NFTs as they affect cognitive performance in the elderly.Brain autopsy data used in this study are from the Honolulu Asia Aging Study (HAAS) of Japanese American men from the state of Hawaii (n=600), and the Nuns Study (NS) of Roman Catholic Sisters largely from the upper midwestern United States (n=378). Cognitive performance within three years of death was assessed by multi-domain dementia rating scales.We found that neocortical neuritic plaque and CAA effects on cognitive performance were mediated by neocortical NFTs for both the HAAS (p < 0.002) and NS (p < 0.043). There were no direct effects of neuritic plaque and CAA after controlling for the mediating effect of NFTs (p > 0.54).These data are consistent with the hypothesis that the association between neuritic plaque and CAA on cognition is mediated by NFT load. This may inform our understanding of the etiology of NFT lesion pathology in aging and AD. The disruption of arterial smooth muscle function by CAA has predictable effects on glymphatic processes and on the regulation of capillary blood flow. These effects are plausibly relevant to the AD neurodegenerative process, and these pathways deserves continued attention by the AD research community.